ANALYSIS ON STUDENTS’ MATHEMATICS ACHIEVEMENT BASED ON LEARNING STYLES - Saija, Louise M (Prodi Magister Pendidikan Matematika Pascasarjana Universitas Pattimura Ambon, 2021)
This descriptive and comparative study aims to see the students learning styles and mathematics achievements. The respondent are fifty junior high school students in Lembang, West Bandung, Indonesia. The research instruments are Perceptual Learning Style Preference Questionnaire (PLSPQ) and mathematics problem solving test. The result of this study are: (1) Only twenty percent of the students have exactly one learning style and most of the students has kinesthetic learning style; (2) Students who have three or less major learning styles perform good mathematics achievement, and students who have minor learning styles only, perform better mathematics achievements averagely, comparing with students who have major learning styles; (3) Students perform better mathematics achievement when they have more than one learning style, (4) There is no significant difference in the students’ mathematics achievement, between students who have three or less major learning styles and students who have more than three major learning styles.